Materials and Device Constructions for Aqueous Lithium–Sulfur Batteries. (30th March 2018) - Yun, Sol; Park, So Hyun; Yeon, Jeong Seok; Park, Jaemin; Jana, Milan; Suk, Jungdon; Park, Ho Seok
Abstract: Lithium–sulfur (Li–S) batteries have advantages in terms of their high specific capacity, natural abundance, and low cost of elementary sulfur on the basis of the multielectron conversion reactions in organic electrolytes. Despite their potential as next‐generation batteries, Li–S batteries are still limited by critical challenges such as redox shuttling and the parasitic reaction of polysulfides arising from intrinsic electrochemistry as well as a low electrical conductivity of sulfur and the insolubility of Li2 S associated with the materials' properties. The unique redox electrochemistry of sulfur in aqueous electrolytes, which is completely different from that in organic electrolytes, provides a rational strategy to resolve the aforementioned problems by the design of new materials and cell constructions. Furthermore, this system enables to achieve significant benefits of aqueous systems in terms of safety, chemical tractability, environmental friendliness, low cost, and high ionic conductivity. Here, at first materials and cell constructions for aqueous Li–S batteries are reviewed, covering the fundamental electrochemistry of sulfur in aqueous electrolytes, the advances in the host materials and aqueous electrolytes, and the cell design of flow‐type aqueous Li–S batteries. Additionally, the current impediments and perspectives into the future direction of this field are provided. Abstract : The key aspects of aqueous Li–S static and flow batteries are comprehensively reviewed focusing on the key aspects of material and device designs. This review covers the fundamental electrochemistry of sulfur in aqueous electrolytes, the advances in the host materials and aqueous electrolytes, and the cell design of hybrid and flow‐type aqueous Li–S batteries.